Structural changes in the retina as a potential biomarker in Parkinson's disease: an approach from optical coherence tomography - Poveda, Santiago; Arellano, Ximena; Bernal-Pacheco, Oscar; Valencia López, Alejandro (Frontiers in Neuroimaging, 2024)
Introduction: Parkinson's disease (PD) presents challenges in early diagnosis and followup due to the lack of characteristic findings. Recent studies suggest retinal changes in PD, is a possibly indicative of neurodegeneration. We explored these changes using optical coherence tomography (OCT) to assess retinal nerve fiber layer (RNFL) and ganglion cell complex (GCC) thickness.Methods: 30 PD and non-PD patients were matched according to demographic characteristics and OCT and clinical evaluations to rule out other neurodegenerative and visual diseases Results: We observed a significant thinning of the RNFL in patients diagnosed with PD compared to non-PD patients (p = 0.015). Additionally, this reduction in RNFL thickness was found to correlate with the severity of the disease (p = 0.04).The OCT serves as a tool for quantifying neurodegeneration in PD, showing a significant correlation with disease severity. These findings suggest that OCT could play a crucial role as a potential biomarker in the diagnosis and monitoring of PD.